ANALISIS EKONOMI POLITIK MEDIA ATAS IDOL GROUP KOREA, BANGTAN BOYS - Sahaka , Fadliani (Jurnal Industri Kreatif dan Inovatif, 2024)
BTS is a South Korean boy band that debuted in the world of entertainment in 2013. Since its debut, this group has become increasingly popular among the world community, so that in 2017 they won the Billboard Music Award with the nomination 'Top Social Artist'. Almost all social media platforms for the band BTS are always trending every time they post videos, photos or even post their personal news. Currently, BTS is even said to be one of South Korea's state assets. In fact, this band is not subject to South Korean military obligations. It was reported that the band would not go to carry out military service, because if they did military service it would mean they would take a break from their work in the world of entertainment and that would affect the country's economy. This research aims to analyze the BTS group from a political economic media perspective. This research uses a descriptive qualitative approach. The results of this research show that BTS displays and introduces Hallyu culture or the Korean Wave of musical arts. This is a form of economic propaganda carried out by South Korea to spread the country's economic and cultural expansion in the arts and culture industry.